Application Of Charak Samhita Matrasitiya Adhyaya (Quantitative Dietetics) In The Maintenance Of Health - Katru, Priyanka; Gupta, Anamika; Narine, Avvinish (International Research Journal of Ayurveda & Yoga, 2020)
Ayurveda is a science based on ancient Indian Philosophy and can be appropriately be called as “The Science of Living”. It has been in existence since the beginning of time. Therefore, in the Charak Samhita, Ayurveda has been described as Shasvata (eternal). Charak Samhita is considered to be the most ancient and authoritative work on Ayurveda available today. Acharya Charak has been referred to as the Father of non-surgical Ayurvedic Indian medicine. The Charak Samhita is most useful for those who wants to improve their health and happiness in life. Ayurvedic Samhitas are considered as a highly codified storehouse of ancient wisdom. Samhitas have their own style of narration and facts have been presented in Shloka form. Commentaries of these Shlokas have been made to explain the meaning of them. Usually, the commentator studies the Shlokas and after critical verification, gives his ideas on the topics. In this article an attempt has been made to accentuate the application of Matrasitiya Adhyaya of Charak Samhita in the maintenance of health.